An Evaluation of the Relationship Between Spatial Form and Transport Mode in Elim, South Africa - Daphne NTLHE (Indonesia Strategic Sustainability, 2023)
The location of activities and the need for interactions create a demand for transport. The mode of transport choices for travelling to commercial centres has always been varied. However, private car use has been the most frequently used mode of transport. As a case study, this study explores how retail trade has influenced transport mode choice in the Elim commercial area in Makhado Local Municipality, South Africa. A mixed method approach was adopted using secondary data and a questionnaire survey to acquire data amongst customers in the Elim commercial area. A Cronbach Alpha test using the survey data was done to check the data’s reliability and internal consistency achieving a Cronbach ? = 0.903, which indicates that the survey data is reliable. The results show that the retail trade area increased in minibus taxis and local people walking to the node where the retail trade is located. The study concluded that the land-use structure in the local area significantly influenced the transportation mode.